Improving Learning Outcomes of Islamic Religious Education Through Card Sort Method for Class VI Students in Mundam Sakti Elementary School 12 - Fatma Liza (BiCED Proceeding, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) for grade VI students of SDN 12 Mundam Sakti through the implementation of the Card Sort method. This method is expected to enhance students' interest and involvement in the learning process, which was previously passive. This research utilizes a classroom action research approach with two cycles. In the first cycle, students' learning outcomes showed that 50% of students were successful, with an average score of 70. After the implementation of the Card Sort method in the second cycle, 100% of students reached the Minimum Mastery Criteria (KKM), with an average score of 80. Based on these results, it can be concluded that the Card Sort method effectively improves students' PAI learning outcomes and motivates them to be more active and engaged in learning.